Genome-Wide Identification and Characterization of Long Non-Coding RNA in Wheat Roots in Response to Ca2+ Channel Blocker - Ma, Keshi; Shi, Wenshuo; Xu, Mengyue; Liu, Jiaxi; Zhang, Feixiong (Frontiers in Plant Science, 2018)
It remains unclear whether plant lncRNAs are responsive to Ca2+-channel blocking. When using the Ca2+-channel blocker, LaCl3, to treat germinated wheat seeds for 24 h, we found that both root length and mitosis were inhibited in the LaCl3-treated groups. The effect of the Ca2+-channel blocker was verified in three ways: a [Ca2+]cyt decrease detected using Fluo-3/AM staining, a decrease in the Ca content measured using inductively coupled plasma mass spectrometry, and an inhibition of Ca2+ influx detected using Non-invasive Micro-test Technology. Genome-wide high throughput RNA-seq and bioinformatical methods were used to identify lncRNAs, and found 177 differentially expressed lncRNAs that might be in responsive to Ca2+-channel blocking. Among these, 108 were up-regulated and 69 were down-regulated. The validity of identified lncRNAs data from RNA-seq was verified using qPCR. GO and KEGG analysis indicated that a number of lncRNAs might be involved in diverse biological processes upon Ca2+-channel blocking. Further GO analysis showed that 23 lncRNAs might play roles as transcription factor (TF); Moreover, eight lncRNAs might participate in cell cycle regulation, and their relative expressions were detected using qPCR. This study also provides diverse data on wheat lncRNAs that can deepen our understanding of the function and regulatory mechanism of Ca2+-channel blocking in plants.